Comparison of the Health Implications on the Use of As and Cd Contaminated Water Supply between Urban and Rural Communities. (3rd November 2014) - Zailina, H.; Najibah, H.; Nadia Aiezzati, A.; Praveena, S. M.; Patimah, I.
Abstract : A cross-sectional study was carried out to determine the arsenic (As) and cadmium (Cd) concentrations in blood, urine, and drinking water as well as the health implications on 100 residents in an urban and a rural community. Results showed the blood As, urinary Cd, DNA damage, and water As and Cs were significantly (P < 0.001 ) higher in the rural community. Findings showed significant (P < 0.005 ) correlations between blood As and DNA damage with household income, years of residence, and total glasses of daily water consumption among the rural residents. The urinary NAG concentrations, years of residence, milk powder intake (glass/week), and seafood intake (per week) were significantly correlated (P < 0.005 ) with urinary Cd concentrations among respondents. In addition, urinary Cd level significantly influenced the urinary NAG concentrations (P < 0.001 ). The rural respondents experienced significantly higher lymphocyte DNA damage and blood As influenced by their years of residence and water consumption. The Cd in drinking water also resulted in the rural respondents having significantly higher urinary NAG which had a significant relationship with urinary Cd.